Radiological abnormalities of the lumbosacral spine in young male individuals - Kamanli, A; Genc, H (Sage Publications Inc, 2002)
The purpose of this study was to determine the overall incidence and distribution of lumbosacral congenital abnormalities in healthy and active young male individuals. The study population consisted of 503 healthy young male candidates for sports training. Lumbosacral transitional vertebral (LSTV) abnormalities were found in 37 (7.4%) of subjects and were unilateral in 14 (2.8%) subjects (lumbarization/sacralization). Lumbar rotoscoliosis (LRS) was present in 14 (2.8%) subjects and facet asymmetry in one subject. LSTV and LRS together were. present in 3 subjects. Spina Bifida Occulta (SBO) was present in 107 of 503:6 1 candidates (21.4%). The distribution of SBO throughout vertebra levels was as follows: 86 only in S1, 11 in S1+S2, 9 in L5, 1 in L5+S1. SBO and LSTV were present together in 8,subjects. SBO and LRS were present together in three subjects. 356,(70.4%) subjects had normal lumbosacral radiographs. Our study results support the notion that SBO is a common lumbosacral abnormality especially in young male healthy individuals.
Keywords: young male; physical deformities; transitional vertebra; spina bifida occulta; low back pain; sport training